1987
DOI: 10.3109/02713688709025231
|View full text |Cite
|
Sign up to set email alerts
|

Bruch's membrane age-related changes vary by region

Abstract: Aging changes known to occur in Bruch's membrane may be associated with drusen formation and retinal pigment epithelial mottling, which often have a peripheral as well as a macular distribution. Few details of peripheral Bruch's membrane aging changes have been reported. We conducted a histochemical investigation of Bruch's membrane in 31 postmortem donor eyes and an ultrastructural morphometric investigation of these regional changes in a subgroup of 22 eyes. The age of our donors ranged from 12 days to 80 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 18 publications
3
50
2
Order By: Relevance
“…In our study, long spacing collagen was observed only when examining the tissues using OTAP thin-sectioning TEM (data not shown). In OTAP images, the long spacing collagens found in BrM demonstrated morphological features similar to those previously described in other studies (Grindle and Marshall, 1978;Newsome et al, 1987).…”
Section: Inclusions Seen In Brm Using Qfdesupporting
confidence: 73%
See 1 more Smart Citation
“…In our study, long spacing collagen was observed only when examining the tissues using OTAP thin-sectioning TEM (data not shown). In OTAP images, the long spacing collagens found in BrM demonstrated morphological features similar to those previously described in other studies (Grindle and Marshall, 1978;Newsome et al, 1987).…”
Section: Inclusions Seen In Brm Using Qfdesupporting
confidence: 73%
“…The long spacing collagen, described in other morphological studies of BrM (Hogan and Alvarado, 1967;Grindle and Marshall, 1978;Killingsworth, 1987;Newsome et al, 1987), was not identified in our QFDE preparations. In our study, long spacing collagen was observed only when examining the tissues using OTAP thin-sectioning TEM (data not shown).…”
Section: Inclusions Seen In Brm Using Qfdementioning
confidence: 61%
“…23,31,32 Moreover, there is evidence that BM fragmentation can trigger proinflammatory responses that might accelerate AMD process. [33][34][35] In addition to BM modifications, drusen deposits, a hallmark of AMD, accumulate between the RPE and BM. Drusens are rich in ECM proteins such as vitronectin (VN) and many inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…Drusens are rich in ECM proteins such as vitronectin (VN) and many inflammatory markers. 23,33,36,37 Thus, one of the important tasks of transplanted hESC-RPE is to produce sufficient ECM to restore the functions of the damaged BM if no BM mimicking nonbiodegradable biomaterial is used with cells. 16,17 Previously, it has been shown that ECM affects the early stage differentiation of hPSCs into neural progenitors and neurons, 38 retinal progenitor cells, 39,40 and RPE cells.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, these BM defects have been described as fragmentation or fracturing in association with calcification (81)(82)(83)(84)(85). Additional age-related changes in BM are typified by: 1) progressive thickening of the two collagenous layers; 2) modification and degeneration of collagen and elastin; 3) increased levels of advanced glycation end products, noncollagenous proteins and lipids; and 4) accumulation of several types of sub-RPE deposits (86)(87)(88)(89)(90)(91)(92)(93)(94)(95). It has also been suggested that the age-related abnormalities in BM eventually lead to photoreceptor degeneration as a result of increased hydrophobicity, reduced permeability, and impaired nutrient exchange between the choroid and the RPE.…”
Section: Morphological Correlates Of Early Amdmentioning
confidence: 99%